2021
DOI: 10.1016/j.celrep.2021.108809
|View full text |Cite
|
Sign up to set email alerts
|

Atx regulates skeletal muscle regeneration via LPAR1 and promotes hypertrophy

Abstract: Highlights d Autotaxin (Atx) is a key regulator of satellite cell function d Conditional deletion of Atx in satellite cells impairs skeletal muscle regeneration d Atx-LPA induces S6K-mTOR signaling via LPAR1 d Atx-LPA promotes muscle hypertrophy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…In this step, muscle stem or satellite cells are isolated from skeletal muscle tissues of mice, cultured to form myoblasts and differentiated further to generate hypertrophic myotubes. LPA is added to differentiating satellite cells to induce hypertrophy as reported in Ray et al. (2021) .…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this step, muscle stem or satellite cells are isolated from skeletal muscle tissues of mice, cultured to form myoblasts and differentiated further to generate hypertrophic myotubes. LPA is added to differentiating satellite cells to induce hypertrophy as reported in Ray et al. (2021) .…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Skeletal muscle regeneration is induced by initiating skeletal muscle injury by the intramuscular injection of cardiotoxin (CTX), a snake venom toxin that induces myofiber damage and a strong regenerative response ( Chargé and Rudnicki, 2004 ; Goddeeris et al, 2013 ; Price et al, 2014 ). Here we describe the steps in induction of muscle injury and initiation of accelerated repair by injecting LPA to regenerating muscles as reported in Ray et al. (2021) .…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent research has revealed that ATX allows fundamental human activity to be conducted and participates in homeostasis and the development of pathological conditions [18,19]. ATX is required during the restoration of muscles by satellite cells, while ATX conditioned ablation or drug inhibition has been shown to impair muscle regeneration [20]. Recent studies have shown that the reconstruction of cartilage in OA temporomandibular joints using extracellular vesicles is mediated via the ATX-YAP signaling pathway [8].…”
Section: Inhibition Of Atx Promoted Lysosomalnumber and Acidity In Oa...mentioning
confidence: 99%
“…Several studies have examined the effect of the LPA1/3 antagonist, specifically Ki16425, administration on energy homeostasis and glucose metabolism in mice with genetic or diet-induced obesity. Based on mRNA analysis, using murine tissues, LPA1 and LPA3 appear to be expressed to a varying extent in insulin target tissues, including WAT, liver, skeletal muscle, and heart [76,79,80]. It has also been shown that LPA receptor levels in these tissues can markedly change during obesity in mice and humans [76,79].…”
Section: Studies Using Pharmacological Lpa Receptor and Atx Modulators And In Situ Atx Silencingmentioning
confidence: 99%